2017
DOI: 10.1093/aobpla/plx067
|View full text |Cite
|
Sign up to set email alerts
|

Drought effects on the tissue- and cell-specific cytokinin activity in poplar

Abstract: Cytokinins are important phytohormones that regulate plant growth. Here we localized cytokinin activities in poplar trees, which are important biomass crops. We demonstrated that even mild drought stress strongly suppresses cytokinin activities in the cambium, the "stem cells" of trees, resulting in loss in productivity and reduced wood formation. Cytokinin activities also decline in the leaf stalks before shedding. Our results identified critical tissues for drought acclimation in the woody biomass crop popla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The differential regulation of these genes across tissues during stress and recovery in gray poplar may reflect different cell growth dynamics. Although water deficiency generally suppresses growth in aboveground poplar tissues, xylem structure and secondary cell wall formation play a central role in avoiding drought damage and are highly regulated (Paul et al, 2017;Sun et al, 2017).…”
Section: Transcription Factors Associated With Stress-related Memorymentioning
confidence: 99%
“…The differential regulation of these genes across tissues during stress and recovery in gray poplar may reflect different cell growth dynamics. Although water deficiency generally suppresses growth in aboveground poplar tissues, xylem structure and secondary cell wall formation play a central role in avoiding drought damage and are highly regulated (Paul et al, 2017;Sun et al, 2017).…”
Section: Transcription Factors Associated With Stress-related Memorymentioning
confidence: 99%
“…In poplar, overexpression of the Arabidopsis CYTOKININ OXIDASE 2, an enzyme involved in cytokinin catabolism, resulted in non-detectable levels of the cytokinin trans-zeatin and its storage form zeatin-O-glucoside and lead to a reduced number of cambial cells, resulting in impaired wood formation [87]. Moreover, cytokinin activity was high in primary meristems supporting its function in early wood formation processes [88] and reduced in the cambial zone of drought stressed poplar, indicating a regulatory function of cytokinins under drought stress [89]. There is now increasing evidence that cytokinins interact with jasmonic acid.…”
Section: Phytohormones Mediate Xylem Changes Under Droughtmentioning
confidence: 99%
“…Another interesting example for drought avoidance is leaf shedding, a common phenomenon in tropical dry forests (Wolfe et al, 2016). Leaf shedding is controlled by an intricate interplay of phytohormones, including ethylene, abscisic acid (ABA), and auxin (González-Carranza et al, 1998; Chen et al, 2002a,b; Jin et al, 2015; Paul et al, 2018), which could be harnessed to improve tree drought resistance. In polyploid poplars regenerated from protoplast fusion accelerated drought-induced leaf shedding was observed that resulted in increased tree survival under extreme drought (Hennig et al, 2015).…”
Section: Introductionmentioning
confidence: 99%